ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP NIAT BERWIRAUSAHA MAHASISWA - Afriyanti Hasanah; Nurhasikin Nurhasikin (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2019)
This study aims to analyze the factors that influence student entrepreneurship intentions. This study uses 260 respondents taken from the students of Business Management Department at Politeknik Negeri Batam who have received entrepreneurial courses. The type of data used in this study is the interval scale, while the scaling method used in the form of likert scale instrument with 4 assessment categories. Data analysis techniques in this study used multiple regression analysis. The results of this study indicate that there are influences of parents’ job, entrepreneurial experience, self efficacy, entrepreneurship education, academic support and social support on student entrepreneurial intentions, while gender and environment support do not affect student entrepreneurial intentions. Future studies are expected to increase the number of research samples, change research samples or add research variables.